How Does the Arctic Sea Ice Affect the Interannual Variability of Tropical Cyclone Activity Over the Western North Pacific? - Fu, Hao; Zhan, Ruifen; Wu, Zhiwei; Wang, Yuqing; Zhao, Jiuwei (Frontiers in Earth Science, 2021)
Although many studies have revealed that Arctic sea ice may impose a great impact on the global climate system, including the tropical cyclone (TC) genesis frequency over the western North Pacific (WNP), it is unknown whether the Arctic sea ice could have any significant effects on other aspects of TCs; and if so, what are the involved physical mechanisms. This study investigates the impact of spring (April-May) sea ice concentration (SIC) in the Bering Sea on interannual variability of TC activity in terms of the accumulated cyclone energy (ACE) over the WNP in the TC season (June-September) during 19812018. A statistical analysis indicates that the spring SIC in the Bering Sea is negatively correlated with the TC season ACE over the WNP. Further analyses demonstrate that the reduction of the spring SIC can lead to the westward shift and intensification of the Aleutian low, which strengthens the southward cold-air intrusion, increases low clouds, and reduces surface shortwave radiation flux, leading to cold sea surface temperature (SST) anomaly in the Japan Sea and its adjacent regions. This local cloud-radiation-SST feedback induces the persistent increasing cooling in SST (and also the atmosphere above) in the Japan Sea through the TC season. This leads to a strengthening and southward shift of the subtropical westerly jet (SWJ) over the East Asia, followed by an anomalous upper-level anticyclone, low-level cyclonic circulation anomalies, increased convective available potential energy, and reduced vertical wind shear over the tropical WNP. These all are favorable for the increased ACE over the WNP. The opposite is true for the excessive spring SIC. The finding not only has an important implication for seasonal TC forecasts but also suggests a strengthened future TC activity potentially resulting from the rapid decline of Arctic sea ice.